Dissemination of Metal Detector Technology for the Geumpang, Pidie Community in Managing Gold Mining Risks - Rahimi, Sayyid Afdhal El; Bernard, Bernard; Lin, Zaw (Jurnal Pengabdian Bakti Akademisi, 2025)
Artisanal and small-scale gold mining (ASGM) activities in Geumpang, Pidie, are commonly practiced using unsafe and unregulated techniques, exposing local communities to environmental and health risks. This community service activity aimed to introduce metal detector technology to enhance safe and effective gold prospecting while reducing mining-related hazards. The program involved 20 local participants and was implemented using a service-learning approach that combined expert-led technical training with participatory community engagement. Hands-on training using Minelab GPX6000 and GPZ7000 detectors was delivered by international practitioners and academic facilitators. The results indicated a 72% improvement in participant knowledge, 85% tool operation proficiency, and a 70% increase in risk awareness. Furthermore, the community proposed a rotational tool-sharing system, demonstrating a commitment to sustainability. The initiative highlights how contextual technology transfer and collaborative training can contribute to safer mining practices and support sustainable development goals in remote mining communities.